Determination of shear strength of self-compacting treated recycled aggregate concrete beam elements. (2022) - Kumar, Mukchand; Ekbote, Anupkumar G.; Singh, Paritosh Kumar; Rajhans, Puja
Abstract: In this investigation, the Shear behaviour of self-compacting recycled aggregate concrete beams using different mixing approaches (NMA and T-S-M-A sfc ) along with treatment of recycled aggregate concrete is studied. In the proposed two stage mixing approach (T-S-M-A sfc ), the silica fume-cement slurry is formed which gives the strength to the interfacial transition zone (ITZ) by filling the pores and cracks. To improve the shear strength of beams treatment of RCA is done by using a coat of sodium silicate along with silica fume. A film of sodium silicate and silica fume is applied on the RCA as a treatment; along with sodium silicate, wherein to make a less permeable recycled aggregate concrete, silica fume is utilized to cover the pores and cracks of RCA. Further, a mix design is proposed named equivalent mortar volume (E-M-V) to improve the shear strength. In the present method, the residual mortar is considered, and the proportion of RCA is decided so that the total mortar content is equal to the mix prepared by a conventional method. The beam's shear strength is determined by obtaining the ultimate load and its corresponding deflection. It is observed that the shear capacity of a beam containing treated RCA shows a better result than that of a beam having untreated RCA despite loading span distance.